Monitoring and controlling the speed and direction of a DC motor through FPGA and comparison of FPGA for speed and performance optimization - Huda M. Abdul Abbas; Raad Farhood Chisab; Mohannad Jabbar Mnati (Institute of Advanced Engineering and Science, 2021)
We are living in the 21st century, an era of acquiring necessity in one click. As we, all know that technology is continuously reviving to stay ahead of advancements taking place in this world of making things easier for mankind. Technology has been putting his part in introducing different projects as we have used the field programmable gate arrays (FPGAs) development board of low cost and programmable logic done by the new evolvable cyclone software is optimized for specific energy based on Altera Cyclone II (EP2C5T144) through which we can control the speed of any electronic device or any Motor Control IP product targeted for the fan and pump. Altera Cyclone FPGAs’ is a board through which we can monitor the speed and direction of the DC motor. As we know how to make understand, dynamic analog input using an A-to-D convertor and we know how to create pulse width modulation (PWM) output with FPGA. Therefore, by combining these two functions we can create an FPGA DC motor controller. Our paper is divided into three parts: First, all of us will attempt to imitate the issue and can try to look for its answer. Secondly, we will try to verify the solution for real-time. In addition, in the last step, we will verify the solution on the real-time measurements.